Crônicas de uma batalha simbólica: as representações neoliberais e suas concorrentes na imprensa argentina (1989, 1991, 2001) - Nascimento, Rodrigo Cerqueira do (2015)
The trajectory of neoliberalism in Argentina is part of a broader context of implementing the thesis of Washington Consensus in most Latin American countries at the end of the 1980s. At the same time, its employment, since the beginning of President Carlos Menem government, represents the abandonment, by the president, of the values related to the Peronist tradition and his alliance to domestic and international groups associated with financial capital. More than a political success, the implementation of structural reforms in Argentina was a symbolic victory, in which social representations associated to neoliberalism were imposed on its competitors to explain the situation and established themselves as a tool to diagnose that crisis, explain its origins and propose solutions to it. This thesis analyzes social representations related to neoliberalism in three relevant Argentine newspapers during three specific moments of its recent history: the election of Carlos Menem to president in 1989; the appointment of Domingo Cavallo as Economy Secretary in 1991, and the implementation of the Convertibility Law; and social and financial crisis that brought down the government of Fernando de la Rúa in December 2001. Using methodological tools developed by content analysis and historically contextualizing references, this investigation examines editorials and opinion notes from Clarín, La Nación and Página/12 to identify the social representations that these newspapers used to discuss the implementation and, then, the crisis of neoliberal reforms project in Argentina under Menem and De la Rúa. The press interpretations about Argentine’s past, the crisis that came up in the 1980s and the projected future for the country accompanied, in large measure, the editorial guidance of these newspapers and their former political tendencies. However, although their original trend remained, the neoliberal thought could impose its agenda to the press and imposed the terms of economic and political debate in most of the period. Without fostering a consensus, Argentina’s media under Menem and De la Rúa reflected the battle of social representations disputing the symbolic power over society in the country at that time